Postemergence weed management in acetolactate synthase (ALS) resistant grain sorghum - Hennigh, David Shane (Kansas State University, 2009)
Field experiments were conducted to evaluate the efficacy of nicosulfuron and nicosulfuron + rimsulfuron applied alone or in combination with various broadleaf herbicides in acetolactate synthase (ALS)-resistant grain sorghum. Herbicides were applied when weeds were 5 to 15 cm in height. Overall weed control was greater when nicosulfuron + rimsulfuron were applied with other herbicides than when it was applied alone. Results indicated that postemergence (POST) application of nicosulfuron and nicosulfuron + rimsulfuron is effective at controlling grasses including barnyardgrass, green foxtail, and giant foxtail. The research also showed that broadleaf weed control was more effective when nicosulfuron + rimsulfuron were applied with other broadleaf herbicides. A field study was conducted to evaluate the differential response of ALS-resistant grain sorghum to POST applications of nicosulfuron + rimsulfuron at three growth stages. Grain sorghum was treated with nicosulfuron + rimsulfuron at the 3- to 5-leaf, 7- to 9-leaf, or 11- to 13-leaf collar stage. Nicosulfuron + rimsulfuron injured grain sorghum when applied at the 3- to 5-leaf, and 7- to 9-leaf collar stage, however, sorghum yields and plant height were only reduced for the 3- to 5-leaf collar stage. Results indicated that nicosulfuron + rimsulfuron application at the 3- to 5-leaf collar stage injured ALS-resistant grain sorghum, but application at 7- to 9-leaf and 11- to 13-leaf collar stages did not result in grain yield reduction. Greenhouse experiments were conducted to evaluate the efficacy, absorption, and translocation of nicosulfuron, rimsulfuron, and nicosulfuron + rimsulfuron. Barnyardgrass, green foxtail, longspine sandbur, and large crabgrass were treated at 5 to 10 cm in height. Barnyardgrass GR[subscript]50 was the lowest and was the most susceptible to all herbicides whereas, large crabgrass had the highest GR[subscript]50 for all herbicides and was the most tolerant. Barnyardgrass and large crabgrass were treated with [superscript]14 C-nicosulfuron, [superscript]14 C-rimsulfuron, or both and radioactivity was recovered at 7 DAT. Barnyardgrass absorption and translocation of nicosulfuron, rimsulfuron and nicosulfuron + rimsulfuron was higher than large crabgrass. Results may indicate that greater absorption and translocation of the herbicides may attribute to the differential response of the species to nicosulfuron, rimsulfuron, and nicosulfuron + rimsulfuron.
Keywords: Grain sorghum; Agriculture, Agronomy (0285)